Specific detection and differentiation of classic goose parvovirus and novel goose parvovirus by TaqMan real-time PCR assay, coupled with host specificity - Wan, Chunhe; Chen, Cuiteng; Cheng, Longfei; Liu, Rongchang; Shi, Shaohua; Fu, Guanghua; Chen, Hongmei; Fu, Qiuling; Huang, Yu (BMC veterinary research, 2019)
Classic goose parvovirus (cGPV) causes high mortality and morbidity in goslings and Muscovy ducklings. Novel GPV (N-GPV) causes short beak and dwarfism syndrome (SBDS) in Cherry Valley ducks, Pekin ducks and Mule ducks. Both cGPV and N-GPV have relatively strict host specificity, with obvious differences in pathogenicity. Specific detection of cGPV and N-GPV may result in false positives due to high nucleotide similarity with Muscovy duck parvovirus (MDPV). The aim of this study was to develop a highly specific, sensitive, and reliable TaqMan real-time PCR (TaqMan qPCR) assay for facilitating the molecular detection of cGPV and N-GPV. After genetic comparison, the specific conserved region (located on the NS gene) of cGPV and N-GPV was selected for primer and probe design. The selected regions were significantly different from MDPV. Through a series of optimization experiments, the limit of detection was 50.2 copies/μl. The assay was highly specific for the detection of cGPV and N-GPV and no cross-reactivity was observed with E. coli., P.M., R.A., S.S., MDPV, N-MDPV, DAdV-A, DEV, GHPV, DHAV-1, DHAV-3, ATmV, AIV, MDRV and N-DRV. The assay was reproducible with an intra-assay and inter-assay variability of less than 2.37%. Combined with host specificity, the developed TaqMan qPCR can be used for cGPV and N-GPV in differential diagnoses. The frequency of cGPV in Muscovy duckling and goslings was determined to be 12 to 44%, while N-GPV frequency in Mule ducks and Cherry Valley ducks was 36 to 56%. Additionally, fluorescence-positive signals can be found in Mule duck embryos and newly hatched Mule ducklings. These findings provide evidence of possible vertical transmission of N-GPV from breeding Mule ducks to ducklings. We established a quantitative platform for epidemiological investigations and pathogenesis studies of cGPV and N-GPV DNA that was highly sensitive, specific, and reproducible. N-GPV and cGPV infections can be distinguished based on host specificity.